Antioxidant activity of Limnophila aromatica Merr. - Arunya Sribusarakum (2017)
The antioxidant properties of methanol extract, essential oil and authentic compounds relating to Limnophila aromatica Merr. essential oil components were investigated employing various established in vitro systems, such as 1,1-diphenyl-2-picrylhydrazyl (DPPH), nitric oxide (NO) radical scavenging and inhibition of lipid peroxidation. The results indicated that methanol extract and essential oil of L. aromatica exhibited free radical scavenger, NO radical scavenger and antilipid peroxidation. The antioxidant activities of methanol extract were higher than essential oil. Eugenol showed antioxidant activity against the radical scavenging ability of DPPH. Eugenol and γ-terpinene also exhibited antilipid peroxidation whereas in the NO scavenging assay, the authentic compounds exhibited weak and no activity.